Aging and Elder Care in Japan: A Call for Empowerment-Oriented Community Development. Issue 7 (16th November 2016) - Inaba, Miyuki
ABSTRACT: This article provides a brief overview of the situation of the elderly and their caregivers in Japan, including demographic changes in Japan, development and changes in long-term care policy that have targeted the poorly integrated community care system, and other challenges that the elderly and family caregivers face. Policy direction designed to address these issues is increasingly targeting care by the community versus support care by society (which was initially the main strategy). The potential of empowerment-oriented community development intervention strategies to decrease the gap between available institutional and formal community-based services and the needs of the elderly and their families in their efforts to meet late life challenges is described. The need for an increased role of social workers in community development interventions is explored and strategies are suggested.